Piecing together the puzzle: nanopore technology in detection and quantification of cancer biomarkers. Issue 68 (4th September 2017) - Vu, Trang; Davidson, Shanna-Leigh; Borgesi, Julia; Maksudul, Mowla; Jeon, Tae-Joon; Shim, Jiwook
Abstract : This mini-review paper is a comprehensive outline of nanopore technology applications in the detection and study of various cancer causal factors. Abstract : Cancer is the result of a multistep process, including various genetic and epigenetic alterations, such as structural variants, transcriptional factors, telomere length, DNA methylation, histone–DNA modification, and aberrant expression of miRNAs. These changes cause gene defects in one of two ways: (1) gain in function which shows enhanced expression or activation of oncogenes, or (2) loss of function which shows repression or inactivation of tumor-suppressor genes. However, most conventional methods for screening and diagnosing cancers require highly trained experts, intensive labor, large counter space (footprint) and extensive capital costs. Consequently, current approaches for cancer detection are still considered highly novel and are not yet practically applicable for clinical usage. Nanopore-based technology has grown rapidly in recent years, which have seen the wide application of biosensing research to a number of life sciences. In this review paper, we present a comprehensive outline of various genetic and epigenetic causal factors of cancer at the molecular level, as well as the use of nanopore technology in the detection and study of those specific factors. With the ability to detect both genetic and epigenetic alterations, nanopore technology would offer a cost-efficient, labor-free and highly practical approach to diagnosing pre-cancerous stages and early-staged tumors in both clinical and laboratory settings.